Terrorism, social media and text mining technique : Review of six years past studies - Kibtiah, Tia Mariatul; Miranda, Eka; Fernando, Yudi; Aryuni, Mediana (Institute of Electrical and Electronics Engineers Inc., 2020)
The aim of this paper is to examine the Islamic State of Iraq and Syria (ISIS) recruitment actual behavior through social media. The ISIS has targeted Indonesia as the main source of participants due to the large of Muslim community with active internet users. Despite many ways to connect with social media like Twitter, Facebook, Instagram, and YouTube using videos and images, this paper is selected text as the main of source of materials. This paper is deployed a qualitative technique to analyze related literature and then it was combined with media tracking systems from texts posted on Twitter, Facebook, Website, and Telegram. The text mining was captured words that frequently appears that mentioned their support to the ISIS accounts from 2011 to 2017. This paper found that Indonesian tends to pay more attention to the existence of ISIS in Syria. This paper suggests that the Indonesian related agency to closely monitor the accounts which positively associated with ISIS terrorism and propaganda and take necessary action to clean up the massive haywire issues.